Click to consult: psychiatrists’ perspectives on how telepsychiatry impacts communication in the emergency department - Shalev, Ligat; Khazen, Maram; Rose, Adam J.; Lubin, Gadi; Eitan, Renana (Frontiers in Psychiatry, 2025)
BackgroundTelepsychiatry, the use of video-calls for evaluation, treatment, or follow-up, is increasingly integrated into psychiatric care. However, research on its impact remains limited, particularly in emergency department (ED) settings where it is used for evaluations considering involuntary psychiatric hospitalization. Little is known about how telepsychiatry influences psychiatrist–patient interactions and the dynamics between attending and resident psychiatrists. This study explores how the transition to telepsychiatry, with the attending psychiatrist evaluating patients remotely while the resident and patient remain in the ED, affects communication and interaction as reported by physicians.MethodsThis qualitative study involved semi-structured interviews with all 36 psychiatrists, including attendings and residents, working in the ED of a psychiatric hospital. Thematic analysis and explanatory content analysis were used. The initial analysis was conducted by one researcher, with two additional researchers independently reviewing the data to ensure trustworthiness.ResultsThree major themes emerged. The first theme focused on changes in psychiatrist–patient communication. Using the CanMEDS Communicator Role framework, we examined how communication patterns shifted with the transition from in-person evaluations to telepsychiatry. Concerns were raised about whether telepsychiatry weakens professionalism and the therapeutic connection between psychiatrists and patients. However, most interviewees considered telepsychiatry sufficient for assessing the need for involuntary hospitalization. The second theme examined residents’ evolving role in telepsychiatry, which has increased their responsibility as mediators in patient evaluations. Without attending psychiatrists physically present, residents must relay crucial sensory and contextual details (e.g., non-verbal cues, odors, prior events) enhancing their clinical judgment and communication skills. The final theme addressed shifts in the attending-resident dynamic. The remote nature of telepsychiatry places emphasis on the degree of trust between attending psychiatrists and residents. Some attendings expressed confidence in their residents’ evaluations, while others raised concerns about potential biases that may arise when attending psychiatrists rely on second-hand information instead of conducting evaluations themselves.ConclusionsThe shift to telepsychiatry changed communication between psychiatrists, residents, and patients, bringing benefits and challenges. These findings underscore how changes in care delivery can impact communication dynamics. This emphasizes the need for telepsychiatry implementation to include ongoing evaluation and training, to maintain effective and ethical care.